Weak approximation of G-expectation - Tolulope Fadina; Frederik Herzberg (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
We refine the discretization of G-expectation by Y. Dolinsky, M.Nutz, and M. Soner (Stochastic Processes and their Applications, 122 (2012), 664-675), in order to obtain a discretization of sublinear expectation where the martingale laws are defined on a finite lattice rather than the whole set of reals.
urn:nbn:de:0070-pub-26753567
Keywords: 330; G-expectation; Volatility uncertainty; Weak limit theorem